COMBINED ANTIHYPERTENSIVE THERAPY IN PATIENTS WITH ARTERIAL HYPERTENSION AFTER THE STROKE - O. A. Ageenkova; V. A. Milyagin; N. Yu. Hozyainova (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To evaluate influence of the combined therapy with ACE inhibitor (perindopril), diuretic (indapamide) and dihydropyridine calcium channel blocker (amlodipine) on ambulatory blood pressure (BP) monitoring indices and heart rate variability in hypertensive patients during early recovery period of stroke.Material and methods. 39 patients (28 men, 11 women) with arterial hypertension of 1-3 degrees during early recovery period after stroke were examined. They received perindopril 10 mg QD, indapamide — 1.5 mg QD. Calcium channel blocker amlodipine (5 mg QD) was added in case of insufficient effect of the ACE inhibitor plus diuretic combination.Results. The combined antihypertensive therapy in hypertensive patients after the stroke led to significant decrease of systolic and diastolic BP (by 23.5% and 18.9%, respectively), normalization of BP daily profile (a number of «dippers» enlarged by 42.2%), improvement of the wall vessel rigidity (decrease in pulse wave velocity by 12.9%) and heart rhythm variability (increase in SDNN, PNN50 and RMSSD by 7%, 20% and 25%, respectively).Conclusion. Advantages of the combined antihypertensive therapy (ACE inhibitor, diuretic, calcium channel blocker) in treatment of hypertensive patients after the stroke are shown.